(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present survey was performed in a town wetland called Sikandarpur Lake in the north west of the city of Muzaffarpur, a metropolis in Bihar. The L-shaped Lake of Sikandarpur (Wetland) is the city’s largest watercourse. It is a ’living lake’ as it connects to the Budhi Gandak River by a pipe. The surface is an average of 60 hectares and the length of the shore lane is 8.1 km. This wetland sits in the centre of an immense farming scenery, over which urbanisation in the town took over. The Municipality of Muzaffarpur is responsible for its care and competence in this wetland. The lake maintains a resource-based integrated practise combining farming and aquaculture which supports the livelihoods of a large, economically deprived population of thousands of lake-dependent families, mainly fish and vegetables. The lake is currently under pressure from various anthropurgical activities in the area, including water diversion, land use modifications, waste water discharges and dumping. It has been one of the most common and rich places in the surrounding area in the past, although aesthetic beauty has deteriorated due to the recent development and population growth. The lake has many environmental problems, eutrophication included. All the bodies of water, including this lake, in the city have the most sewage and are poorly managed and attract the most humane intervention. The lake now includes about 6 drainage points, one of the main causes for water depletion. Adequate guidelines for implementing successful monitoring systems with the involvement of appropriate management policy must be established to reduce the current rate of degradation of wetlands. A analysis of the wetlands in the city of Muzaffarpur identifies a range of main issues and offers appropriate management requirements for the sustainable use of wetlands.